Integrative review of the use of wood through the wood frame constructive system in Brazil (Research, Society and Development, 2022)
The wood frame presents itself as a great ally with civil construction, its advantages in relation to speed and efficiency in constructions, in addition to all sustainable requirements, has been conquering even more those looking for alternative means of construction. Thus, the aim of this study was to describe the wood frame considering its sustainable aspects, its construction technique, its use in Brazil, as well as the advantages and disadvantages, in addition to comparatives in relation to conventional masonry. To carry out this work, an integrative literature review was carried out. Few articles were found that addressed the wood frame in a more complete and aggregated way. Thus, in order to bring a broader study, considering points of great relevance to the wood frame, 56 references were gathered to support this study. Contributing to the presentation of how sustainability needs to be present in constructions, evidences of wood frame in Brazil, as well as the importance of using this method for social, environmental and economic issues. Committed to popularizing and accepting this construction technique, clarifying its effectiveness and reliability as a structural material for buildings. Concluding that Brazil has a great advantage in the implantation of the wood frame, considering also that this system is superior in sustainable concepts.